Effects of part and whole straw returning on soil carbon sequestration in C3–C4 rotation cropland. Issue 3 (25th March 2019) - Liu, Zhen; Gao, Tianping; Liu, Wentao; Sun, Kai; Xin, Yanni; Liu, Hongjian; Wang, Shengzhao; Li, Geng; Han, Huifang; Li,, Zengjia; Ning, Tangyuan
Abstract: Long‐term no‐tillage management and crop residue amendments to soil were identified as an effective measure to increase soil organic carbon (SOC). The SOC content, SOC stock (SOCs), soil carbon sequestration rate (CSR), and carbon pool management index (CPMI) were measured. A stable isotopic approach was used to evaluate the contributions of wheat and maize residues to SOC at a long‐term experimental site. We hypothesized that under no‐tillage conditions, straw retention quantity would affect soil carbon sequestration differently in surface and deep soil, and the contribution of C3 and C4 crops to soil carbon sequestration would be different. This study involved four maize straw returning treatments, which included no maize straw returning (NT‐0), 0.5 m (from the soil surface) maize straw returning (NT‐0.5), 1 m maize straw returning (NT‐1), and whole maize straw returning (NT‐W). The results showed that in the 0–20 cm soil layer, the SOC content, SOCs, CSR and CPMI of the NT‐W were highest after 14 years of no‐tillage management, and there were obvious differences among the four treatments. However, the SOC, SOCs, and CSR of the NT‐0.5 and NT‐W were the highest and lowest in 20–100 cm, respectively. The value of δ 13 C showed an obviously vertical variability that ranged from –22.01‰ (NT‐1) in the 0–20 cm layer to –18.27‰ (NT‐0.5) in the 60–80 cm layer, with enriched δ 13 C in the 60–80 cm (NT‐0.5 and NT‐1) and 80–100 cm (NT‐0 and NT‐W) layers. The contributions of the wheat and maize‐derived SOC of the NT‐0.5, NT‐1 and NT‐W increased by 11.4, 29.5 and 56.3% and by 10.7, 15.1 and 40.1%, relative to those in the NT‐0 treatment in the 0–20 cm soil layer, respectively. In conclusion, there was no apparent difference in total SOC sequestration between the NT‐0.5, NT‐1, and NT‐W treatments in the 0–100 cm soil layer. The contribution of wheat‐derived SOC was higher than that of maize‐derived SOC.